Adaptive responses of sterically confined intramolecular chalcogen bonds. Issue 35 (9th August 2018) - Selvakumar, Karuthapandi; Singh, Harkesh B.
Abstract : The existence of intramolecular chalcogen bonds (IChBs) in 2, 6-disubstituted arylchalcogen derivatives is determined by the substituents and the sigma hole donor behavior of the chalcogen atom in the molecule. Abstract : The responsive behavior of an entity towards its immediate surrounding is referred to as an adaptive response. The adaptive responses of a noncovalent interaction at the molecular scale are reflected from its structural and functional roles. Intramolecular chalcogen bonding (IChB), an attractive interaction between a heavy chalcogen E (E = Se or Te) centered sigma hole and an ortho -heteroatom Lewis base donor D (D = O or N), plays an adaptive role in defining the structure and reactivity of arylchalcogen compounds. In this perspective, we describe the adaptive roles of a chalcogen centered Lewis acid sigma hole and a proximal Lewis base (O or N) in accommodating built-in steric stress in 2, 6-disubstituted arylchalcogen compounds. From our perspective, the IChB components (a sigma hole and the proximal Lewis base) act in synergism to accommodate the overwhelming steric force. The adaptive responses of the IChB components are inferred from the observed molecular structures and reactivity. These include (a) adaptation of a conformation without IChBs, (b) adaptation of a conformation with weak IChBs, (c) twisting the skeletal aryl ring while maintaining IChBs, (d) ionization of the E–X bond ( e.g., X = Br) to relieve stress and (e) intramolecular cyclization to relieve steric stress. A comprehensive approach, involving X-ray data analysis, density functional theory (DFT) calculations, reaction pattern analysis and principal component analysis (PCA), has been employed to rationalize the adaptive behaviors of IChBs in arylchalcogen compounds. We believe that the perception of ChB as an adaptive/stimulus responsive interaction would profit the futuristic approaches that would utilise ChB as self-assembly and molecular recognition tools.